1975
DOI: 10.1021/j100572a017
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin resonance studies of anisotropic rotational reorientation and slow tumbling in liquid and frozen media. III. Perdeuterated 2,2,6,6-tetramethyl-4-piperidone N-oxide and an analysis of fluctuating torques

Abstract: Publication costs assisted by the Petroleum Research Fund A detailed analysis of line shapes and relaxation is made for the perdeuterated 2,2,6,6-tetramethyl-4-piperidone AT-oxide (PD-Tempone) nitroxide radical covering the whole range from fast motional narrowing (tr ~10-12 sec) to the rigid limit (tr ~10-6 sec) in several deuterated solvents. The slow tumbling resultsshow particularly good agreement with the slow tumbling theory of Freed, et ai, for a reorientational model of moderate jumps (ca. 50°r ms), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
233
1
3

Year Published

1977
1977
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(266 citation statements)
references
References 15 publications
29
233
1
3
Order By: Relevance
“…In this approach, the stochastic Liouville equation for the spindensity matrix was modified to consider the effects of Brownian anisotropic rotational diffusion upon EPR and ST-EPR lineshapes. This treatment was similar to that reported by Freed et al (17), who also found that meaningful simulation of experimental spectra was greatly facilitated by perdeuteration of the spin label 2,2,6,6-tetramethyl-4-piperidone-l-oxyl (PDtempone) (18 All incubations were at 2°C.…”
Section: Methodssupporting
confidence: 83%
“…In this approach, the stochastic Liouville equation for the spindensity matrix was modified to consider the effects of Brownian anisotropic rotational diffusion upon EPR and ST-EPR lineshapes. This treatment was similar to that reported by Freed et al (17), who also found that meaningful simulation of experimental spectra was greatly facilitated by perdeuteration of the spin label 2,2,6,6-tetramethyl-4-piperidone-l-oxyl (PDtempone) (18 All incubations were at 2°C.…”
Section: Methodssupporting
confidence: 83%
“…The A and z values determined for the II and I orientations for the hydrated systems ( Table 1) are indicative that the probe is tumbling more rapidly about one molecular axis than about others. In isotropic media, asymmetry in tumbling is expected because of the axially symmetric ellipsoid shape of the probe (Hwang et al, 1975); however, * Broad X-ray diffraction peak representing random interstratification.…”
Section: U; mentioning
confidence: 99%
“…There is some evidence from X-ray powder diffraction data (Table 2) that the more weakly hydrating exchange cations permit smaller interlamellar spacings, thereby reducing the volume available for molecular rotation. The effective rotational diameter of the spin probe is about 6.5 A (Hwang et al, 1975), so that tumbling in a ~ 10• wide interlayer might be expected to be somewhat restricted.…”
Section: U; mentioning
confidence: 99%
“…Adding power P as a new dimension provides enough information to determine R 1 , in addition to R 2 , and Γ G (73,(75)(76)(77)(78)(79)(80)(81), thus achieving our primary goal of accurately determining relaxivities χ 1 . Small nitroxides in deoxygenated solution exhibit discrete superhyperfine splitting.…”
Section: Eq 13mentioning
confidence: 99%